The Effect of the Realistic Mathematics Education Approach on Students' Mathematical Communication Skills - Melda andini; Nurhanurawati; Santy Setiawati (Universitas Teknokrat Indonesia, 2026)
This quasi-experimental research was conducted to examine the influence of the Realistic Mathematics Education (RME) approach on students’ mathematical communication abilities. The population of the study included all eighth-grade students of SMP Negeri 5 Bandar Lampung in the odd semester of the 2025/2026 academic year, consisting of 285 students. The research sample was determined through purposive sampling, involving class VIII.6 with 30 students as the experimental group and class VIII.7 with 31 students as the control group. The study applied a pretest–posttest control group design. Quantitative data on students’ mathematical communication skills were collected using a written test. The data were analyzed using descriptive statistical techniques and inferential analysis with a t-test. The findings revealed that students taught using the RME approach demonstrated a greater improvement in mathematical communication skills compared to those who received conventional instruction. Thus, it can be concluded that the application of the RME approach has a significant positive effect on students’ mathematical communication skills.